Análise das propagandas dos medicamentos isentos de prescrição veiculadas em revistas para prescritores na área médica - Guanaes, Lais Danciguer; Coque, Jacqueline Rico; Hipólito Junior, Edson; Guarido, Cristiane Fátima; Mastroianni, Patricia de Carvalho [UNESP]; Rossignolli, Patrícia de Souza (My University, 2012)
This article presents an analysis of the quality of advertisements for over-the-counter (OTC) drugs addressed to the medical profession, based on the new Anvisa resolution RDC 96 (17/12/2008). For this analysis, 16 volumes of the Brazilian Journal of Medicine (RBM) were collected, from August 2009 to December 2010. To investigate the quality of the adverts, we prepared a questionnaire divided into three parts. In total, 160 advertisements were found, of which 27 were related to drugs exempt from prescription, from 9 laboratories. It was observed that none of the advertisements complied fully with the new rules, as required by legislation (RDC 96/08), with violations ranging from identification of the advert to prohibitions of human figures and subjective messages. Therefore, it was concluded that there is a need to implement more effective monitoring, so as to improve the quality of the adverts, so they can be used as a reliable source of information and update by prescribers.

O presente artigo apresenta uma análise da qualidade das propagandas de medicamentos isentos de prescrição destinadas à classe médica, baseado na nova RDC no96, de 17 de dezembro de 2008. Para análise coletou-se 16 fascículos da Revista Brasileira de Medicina (RBM) a partir de agosto 2009 a dezembro de 2010. Para averiguação da qualidade, elaborou-se um questionário dividido em três partes. Ao todo 160 peças publicitárias foram encontradas, em que 27 delas eram referentes aos medicamentos isentos de prescrição, contemplando nove indústrias farmacêuticas. Observou-se que nenhuma das peças publicitárias cumpriu na íntegra as novas regras exigidas na legislação vigente (RDC 96/08), apresentando infrações desde identificação da mesma até as proibições de figuras humanas e mensagens subjetivas. Portanto, concluiu-se que: há necessidade de implantação de um instrumento mais efetivo de fiscalização, a fim de melhorar à qualidade das propagandas para poderem ser usadas como fonte fidedigna de informação e atualização aos prescritores.
Analysis of advertisements for OTC drugs aimed at prescribers in the medical field
Keywords: Advertising; Legislation; OTC drugs; non prescription drug; advertizing; human; law; medical profession; prescription; questionnaire